Translation and adaptation of adult self report: a tool for assessment of adult psychopathology - Saira Khan; Anila Kamal (Journal of the Pakistan Medical Association, 2021)
Objective: The objective of present research is to translate, adapt and validate Adult Self-Report (ASR) in to Urdu language. It also intends to establish internal consistency of subscales of ASR. Methods: The preset correlational cross sectional study was conducted during the time period of September 2017 to August 2018 at National Institute of Psychology, Quaid-i-Azam University Islamabad. Employing non-probability convenience sampling technique data was collected from 768 participants, including 408 seeking treatment in psychiatric outpatient services and 360 non-clinical sample. Results: The eight syndrome model proposed earlier for ASR was tested and confirmed for Pakistani sample. The values of RMSEA (.03), CFI (.94) and TLI (.94) indicated good model fit. All items indicated good factor loadings ranging from .25 to .94. Reliability analysis indicated that all subscales were internally consistent with alpha reliabilities ranging from .64 to .92. Conclusion: Adult self-report is a comprehensive tool that shows a good model fit with Pakistani sample. It has sound psychometric properties and can be effectively used for the assessment of adult psychopathology. Keywords: Adult Self Report, Confirmatory factor Analysis, Adult Psychopathology, Achenbach system of empirically based taxonomies, Continuous...